The Square cup deep drawing: Technology transfer from experts to increase production in small and medium enterprise (SME) groups - Karyadi Karyadi; Sukarman Sukarman; Dodi Mulyadi; Muhamad Taufik Ulhakim; Nazar Fazrin; Tomas Irfani; Nana Rahdiana; Afif Hakim; Alizar Nurdin; Fajar Mucharrom (Mechanical Engineering for Society and Industry, 2024)
The deep drawing is a complex steel forming method involving blank dimensions, dimension/height ratio (D/H ratio), and clearance between die and punch (D/P allowance). Failure to identify proper blank dimensions and D/H ratio can lead to production defects such as tears, while failure to recognize the correct clearance can cause wrinkles. This article discusses technology dissemination to Small and medium-sized enterprises (SMEs) for the deep drawing process in producing R-ornament components #3D40x40, considering these crucial parameters. R-ornament #3D40x40 was manufactured using SPCC-SD material with a thickness of 0.65 mm. The Participatory Action Research (PAR) method was employed to collaboratively optimize blank dimensions, D/H ratio, and dies/punch (D/P) allowance with partners. The optimization of blank dimensions successfully eliminated the need for the trimming process, resulting in reduced investment costs in dies and die setup by IDR 15 million and 2.16 million, respectively. Identifying a D/H ratio of 1.32 successfully eliminated tear defects and determining a D/P allowance of 0.87 mm on each side eradicated wrinkle defects in the product. This article contributes to Goal 9 of the Sustainable Development Goals (SDGs), specifically focusing on the Small and Medium-sized Enterprises (SMEs) sector.